Перспективы существования молодых государств в зоне пересечения стратегических и геополитических интересов на примере существования Дальневосточной республики (1920-1922 гг.) - Литвинов, В.В. (Культура народов Причерноморья, 2013)
В исследовании раскрываются особенности положения русского Дальнего Востока после
окончания гражданской войны в ноябре 1922 года. В дослідженні розкриті особливості стану Російського Далекого Сходу після завершення
громадянської війни в листопаді 1922 р. The author continued investigated history the Russian Far East, when bad known in the Ukraine
know. The essence developing the Far East lands after 1922 are discovered in this research work. Neither 5
years of civil war not different displays of foreign policy had this process impeded. Author analyzing Japan
economic expansion and Far East region economic at 1920-1924. Author analyzing Japan and China foreign
policy territory and military pretension’s to Russian Far East region. In this situation author draw a conclusion
that existence independent state – The Far East Republic was impossible.